A participação dos pais no processo de alfabetização: acompanhamento de estudo - Machado, Edna Mariana (1994)
This study was developed from the perspective of the cognitive-developmental approach, researching the monitoring of parents over the student's school life as one of the factors that influence their performance. Field research was carried out in two schools in Uberlândia, one state and one private, with literacy classes. Interviews and questionnaires applied to teachers, principals, students and parents in relation to the various aspects of: school activities, highlighting the tasks determined "For Home". It was concluded that the parents, in general, do not satisfactorily follow the would come from their children's school and that, according to the perception of teachers and principals, students would have better income if there was more effective parental participation in the monitoring their children's school life.